2008
DOI: 10.1016/j.pedn.2007.08.001
|View full text |Cite
|
Sign up to set email alerts
|

The Lived Experience of Fathers Who Have Children With Asthma: A Phenomenological Study

Abstract: Asthma is the most common chronic illness of childhood. It is a leading cause of school absenteeism and accounts for a major portion of pediatric admissions to emergency departments and hospitals. When a child is diagnosed with asthma, parents become responsible for the long-term management of a chronic condition that may be characterized by unpredictable and irregular episodes.Most of the research concerning parents and childhood asthma is focussed on mothers. The small number of studies in which mothers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 30 publications
(83 reference statements)
1
52
0
Order By: Relevance
“…Consequently, parents develop considerable expertise in managing their child's long-term condition (Bailing & McCubbin, 2001: Dickinson et al, 2006: Nuutila & Salanterä, 2006. The process of developing this expertise has been described as blending knowledge and skill acquisition with experiential knowledge in order to adapt to changes in the child's condition (Bailing & McCubbin, 2001;Cashin, Small & Solberg, 2008;Smith, et al, 2013b). Moving from a novice to an expert is not solely achieved by gaining experience and knowledge but is a process of change and involves developing the skills to critically analyse new situations and effectively problem-solve (Dryfus & Dryfus, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, parents develop considerable expertise in managing their child's long-term condition (Bailing & McCubbin, 2001: Dickinson et al, 2006: Nuutila & Salanterä, 2006. The process of developing this expertise has been described as blending knowledge and skill acquisition with experiential knowledge in order to adapt to changes in the child's condition (Bailing & McCubbin, 2001;Cashin, Small & Solberg, 2008;Smith, et al, 2013b). Moving from a novice to an expert is not solely achieved by gaining experience and knowledge but is a process of change and involves developing the skills to critically analyse new situations and effectively problem-solve (Dryfus & Dryfus, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Actively involving parents in care decisions, and children and young people as appropriate, is particularly salient in the context of long-term conditions where the day-to-day management of care becomes primarily the responsibility of the family. Evidence suggests that care-giving such as providing medical and nursing interventions above usual parenting tasks is a significant feature of living with a child with a long-term condition for both fathers and mothers (Cashin, Small & Solberg, 2008;Smith, Cheater & Bekker, 2013a;Wennick & Hallström, 2007). In order to manage their child's condition, parents need to; gain knowledge of the condition and treatments (Bailing & McCubin 2001;Knafl, Deatrick, Knafl, Gallo, et al, 2013, Nuutila & Salanterä, 2006; learn how to identify and respond to illness symptoms in their child (Smith, Cheater, Bekker & Chatwin, 2013b;Wennick & Hallström, 2007); and develop effective relationships with health professionals (Dickinson, Smythe, & Spence, 2006;Swallow & Jacoby, 2001;Swallow, Lambert, Santacroce, Macfadyen, 2011;Swallow, Macfadyen, Santacroce & Lambert, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Emotional and service-related support from partners, extended family, and friends were common findings in the literature (Cashin, Small, & Solberg, 2008;Desai et al, 2016). However, the ʻohana in the study appeared to be a much larger network of involved relatives than listed in the literature (Cashin et al, 2008).…”
Section: Discussionmentioning
confidence: 54%
“…In the face of uncertainty, the findings in this study and existing literature described several coping strategies used by participants such as vigilance (Cashin et al, 2008) and information seeking (Cashin et al, 2008;Desai et al, 2016;Swallow et al, 2011). Also, the study identified two types of therapies utilized by native Hawaiians: Western therapies and CAM remedies.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation